Development of Student Work Sheet Based Realistic Mathematics Education (RME) on Polyhedron Topic - Fella Megri Oktavani; Dewi Yuliana Fitri; Lucky Heriyanti Jufri (Rangkiang Mathematics Journal, 2023)
The background of this research is that the teaching materials in Sijunjung 7 Public Middle School have not been able to make students become active and accustom students to independent learning in solving problems given by the teacher. This study aims to develop Student Worksheets (LKPD) based on Realistic Mathematics Education (RME) in class VIII SMP Negeri 7 Sijunjung that are valid and practical. The development procedure used is the plomp development model which consists of 3 stages, namely preliminary research, prototyping phase, and assessment phase. Teaching materials expected by students are teaching materials that make students active in the learning process and are able to guide students to learn independently. The instruments used are validity questionnaires and practicality questionnaires. Based on the data analysis it was concluded that the LKPD developed was in very valid criteria with an average of 85.7%. The results of the practicality questionnaire analysis based on small group evaluations of 6 students obtained an average of 87.79% with very practical criteria. The conclusion of this research is to produce worksheets based on Realistic Mathematics Education that are valid and practical on flat sided geometric material in class VIII SMP Negeri 7 Sijunjung.